Clinically important change for the FACIT-Fatigue scale in paroxysmal nocturnal hemoglobinuria: a derivation from international PNH registry patient data - David Cella; Peter Johansson; Yasutaka Ueda; Ioannis Tomazos; Philippe Gustovic; Alice Wang; Ami S. Patel; Hubert Schrezenmeier (SpringerOpen, 2023)
Abstract Background Fatigue is the most common symptom associated with paroxysmal nocturnal hemoglobinuria (PNH). The objective of this analysis was to estimate values that would suggest a clinically important change (CIC) for the functional assessment of chronic illness therapy-fatigue scale (FACIT-Fatigue) in patients with PNH. Methods Adults with PNH who initiated eculizumab within 28 days of enrollment in the International PNH Registry as of January 2021 with baseline FACIT-Fatigue scores were included in the analysis. Distribution-based estimates of likely difference were calculated using 0.5 × SD and SEM. Anchor-based estimates of CIC considered the European Organization for Research and Treatment of Cancer (EORTC) global health status/quality of life summary score and the EORTC Fatigue Scale score. Changes in anchors and high disease activity (HDA) shift from start of eculizumab treatment to each follow-up visit were then assessed by FACIT-Fatigue score change (≤ 1 CIC, no change, or ≥ 1 CIC). Results At baseline, 93% of 423 patients had fatigue documented in their medical history. The distribution-based estimates for FACIT-Fatigue were 6.5 using 0.5 × SD and 4.6 using SEM; internal consistency was high (α = 0.87). For anchor-based estimates, the FACIT-Fatigue CIC ranged from 2.5 to 15.5, and generally supported 5 points as a reasonable lower end of the value for meaningful individual change. The percentage of patients who changed from having HDA at baseline to no HDA at eculizumab-treated follow-up visits increased over time. Conclusion These results support the use of 5 points as the CIC for FACIT-Fatigue in patients with PNH, which is within range of the CICs reported in other diseases (3-5 points).